PENGARUH KEPEMIMPINAN DAN PEMBIAYAAN PENDIDIKAN TERHADAP HASIL UJI KOMPETENSI KEAHLIAN SMKN 1 SIMPANG HILIR - Sahid, Muhammad; Ulfa, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Expertise Competency Test (UKK) is part of goverment intervention in ensuring the quality of education in Vacational High School education units. However, ths role is still less than optimal in terms of equility, relevance, effectiveness, effeciency, and quality of education itself. Essentially, it is the ability of human resources to determine the result obtained from education. This thesis is entitled ?The Effect Of LeadershipAnd Aducation Finance On The Outcomes Of Expertise Competency Test At State Vacational High School 1 In Simpang Hilir Northertn Kayong Regency?. This study aims tu analyze the importance of leadership an education funding on the result of the XII grade students? competency test in Vacational High School 1 At Simpang Hilir. Based on the research findings, it can be perceived that the magnitude of the result forthe coefficienton leadership variables is determined by the value of sig < 0,05 or Tcount > T-table which is 0,003<0,05 or 1,737>1,66. This indicates that the leadeship variabel inself (partial) has a direct and significant effect on the result of the expertise competency test, with and effect of 25% on the result. Meanwhile, on the financing variabel, it can be discerned that the magnitude of the results is 0,036<0,05 or 1,790>1,66. This shows that the educational funding variabel itself (partial) has a direct and significant effect on the result of the expertise competency test with an influence of 67,24% on the result. Furthermore, from the testing together (simultaneous) of the leadership variabels and educational funding, obtained F-count >F-table that is equal to 38,8>1,66, this determines that the variabel of ladership and educational funding directly influence the result of the expertise competency test, which is 38,8%.Keywords: Leadership, Education Financing, Expertise Competency Test